Strategi Pemasaran Digital Pada Hotel Grand Inna Medan Menggunakan Analisis STP - Iksan Manurung, Muhammad Rizky (Politeknik Pariwisata Medan, 2025)
This qualitative research aims to identify the market segmentation of the Grand Inna Medan Hotel, encompassing geographic, demographic, behavioral, and psychographic variables, as a basis for formulating a more targeted STP-based digital marketing strategy. The scope includes an analysis of historical booking documents (Q3-Q4 2025) and digital activities on three main channels (official website, Instagram, TikTok), with a marketing budget below IDR 1 million per segment. Data was collected through semi-structured interviews with eight key informants (marketing managers, loyal guests, travel influencers, front-desk staff) and observations of content and user interactions on digital platforms. Data analysis used thematic coding to map the characteristics of each segment and their primary needs. The results are expected to map three to five key customer segments, such as